Choroidal thickness in primary angle-closure glaucoma: the results of Measurement by Means of Optical Coherence Tomography - N. I. Kurysheva; M. A. Boyarinceva; A. V. Fomin (Oftalʹmologiâ, 2014)
Purpose: to compare сhoroidal thickness (CT) in primary angle-closure glaucoma (PACG) and primary open angle glaucoma (POAG).Methods: сhoroidal thickness was evaluated in 30 patients (30 eyes) with PACG, 30 patients (30 eyes) with POAG and 30 control subjects by means of optical coherence tomography (RTVue-100 OCT, Optovue, Inc., Fremont, CA) in fovea (CTf) and in peripapillary region (CTp). Patients in both groups were well matched for glaucoma stage (MD 1,46±1,73 dB in POAG and –1,89±2,34 dB in PACG, p = 0,44) and age: 70,0±6,64 in POAG and 68,0 ±4,68 in PACG (p = 0,29).Results revealed a statistically significant increase of CT in PACG patients in comparison to POAG: 372,81±126,83 μm and 251,25±79,56 μm (p = 0,002), respectively for CTf, and 204,56±115,9 μm and 29,0±61,48 μm (p = 0,03), respectively for CTp.Conclusion: Increased CT might be another anatomic characteristic of AC eyes. These findings may support the hypotheses that choroidal expansion is a contributing factor to the development of AC disease.